Pengembangan E-modul Praktikum Kimia Dasar Menggunakan Aplikasi Canva Design - Kana Puspita*; Muhammad Nazar; Latifah Hanum; Muhammad Reza (Universitas Syiah Kuala, 2021)
The implementation of learning has undergone significant changes due to the corona virus (Covid-19) spreading rapidly so that the teaching and learning process at various levels of education is generally carried out online. This urges lecturers to adapt teaching materials to online learning systems, especially subject topics that require laboratory activities. This study aims to develop an e-module for basic chemistry practice courses not only containing material and quizzes but also integrates practical video tutorials in each of its sub-topics. The research method used is research and development (RD) by applying the ADDIE model. Research respondents were 58 students of the Physics Education FKIP USK wenrolled in basic chemistry practice courses in their first-year study in the 2019-2020. The research data were collected using instruments in the form of students’ responses to the questionnaire on 1) the e-module, and 2) the application of e-modules in basic chemistry laboratory courses. The questionnaires were distributed via Google form to avoid physical contact and comply with health protocols. Prior to distribution, the questionnaire was tested for validity and reliability using the Cronbach's alpha test and analyzed with SPSS version 12 (IDMTM). The results of the validation show that the mean value of validation is 91.48% for the display, content, grammar, and evaluation system items. Cronbach's alpha test shows a mean alpha value of 0.903. The results of the response questionnaire showed that the average response score was greater than 8.00 for each questionnaire item, while the mean score for the application of the e-module laboratory courses was 8.88. This shows that the e-module for basic chemistry lab work is favorable and suitable for use as teaching material in the online learning process.